Cultural protection of Taijiquan from the perspective of Human Intangible Cultural Heritage - Chen, Fei; Wang, Hongwei (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: The huge transformation of human society poses a huge challenge to the protection of culture. In recent years, increasing attention is paid to the protection of intangible cultural heritage worldwide. In 2020, Taijiquan was included in the UNESCO List of Intangible Cultural Heritage of Humanity. This is of great significance to the inheritance of Chinese martial arts and even the excellent traditional culture of the Chinese nation. The core of Taijiquan is no longer the public’s understanding of "wu", but it is used as a "cultural" symbol to continue in the future development of mankind. In order to promote the inheritance and protection of Taijiquan culture, from the perspective of the protection of human intangible cultural heritage and starting from the reality, research on the protection of Taijiquan culture. Methods: Use the literature data method to sort out related literature on intangible heritage protection and Taijiquan culture. The expert interview method is mainly used to conduct interviews on issues such as the productive protection of intangible cultural heritage and the protection methods and approaches of Taijiquan cultural heritage. Results: 1) Clarify that the core symbol of Taijiquan is the key to cultural protection and inheritance. What is Tai Chi? A kind of sports, a martial arts system, or a national spirit carrier that advocates self-cultivation. No matter what is promoted or researched, we must first understand what its core symbol is. This is the prerequisite for clarifying what Taijiquan intangible cultural heritage should be protected. Obviously the cultural value of Taijiquan is its core element and is an indispensable content to reflect the vitality of Taijiquan. 2) Development is the last word in the protection of intangible cultural heritage. The formation of Taijiquan relies on China’s natural geography and social and cultural background. Currently, Taijiquan, as an intangible cultural heritage, has undergone tremendous changes in its habitat, and its changes are also rationale. As it should be, therefore, whether intangible cultural heritage conventions or folklore, hey recognize and encourage this kind of change and living inheritance. Looking back at the production of Chen-style Taijiquan, the so-called farming in busy time and creating boxing in free time. This process of creating boxing is the evolution or imagination of Chen Wangting in his mind based on his own actual combat experience. It is an extract of the personal training method of exercising martial arts for the purpose of fight. With the development of the times, the reform of boxing for different consumption objects is the driving force to promote its popularization and development. For example, Yang Luchan aimed at nobles not suitable for high-intensity physical activity, transformed Chen-style Taijiquan into aristocratic consumption objects, and simplified Taijiquan was created for mass fitness, and rehabilitative production of Taijiquan in the face of patients. This is the development of Taijiquan seeking self-development or adapting to the market conditions. This change is worthy of recognition and recognition, whether it is for the purpose of adapting to local conditions or for sustainable purposes, and it has a positive role in promoting the development of traditional martial arts. 3) The cultural protection of Taijiquan not only maintain the ontological image but also advance with the times for innovative development. Maintaining the original characteristics of Taijiquan is the foundation for its survival, but from the perspective of intangible cultural heritage protection, the excessive obsession with the development of the real society is not encouraged, and it must not lie on the historical credit. After a long period of development, Taijiquan has risen from primitive martial arts to a higher level of pursuit. The interpretation of Taiji reflects traditional Chinese wisdom. With the development of society, Taijiquan must be grasped in the changes of the times. The direction of its development is to seek innovative development in cultural protection. The "Convention for the Protection of Intangible Cultural Heritage" defines protection with rich connotations. It is not only guard in a simple sense, but is based on traditional practices and the changes in the material and cultural environment. This innovation implies with a strong sense of inheritance, promotion and revitalization. Therefore, the protection and innovation of Taijiquan in the context of the new era should interpret the relationship between the two in the context of the Convention for the Protection of Intangible Cultural Heritage, adhere to the traditional wisdom of Tai Chi culture, and use traditional wisdom to solve new problems. Realizing the modernization of traditional wisdom is an important way to protect tradition and innovative development. 4) The protection of inheritors is an important means of intangible cultural heritage protection. Inheritance is the core of intangible cultural protection, so that valuable human culture can last forever, and inheritors are the focus of intangible cultural heritage protection. The protection of inheritors should not only pay attention to the inheritance of skills and avoid the disappearance of skills after death, but also pay attention to the cultivation of inheritors, which is of great significance to the self-evidence of this type of boxing and the development of Taijiquan. Conclusion: As the intangible cultural heritage of mankind, Taijiquan is full of the genes and national wisdom of traditional Chinese culture. Interpreting the cultural protection of Taijiquan from the perspective of intangible heritage is for the healthy development of Taijiquan and for enhancing the cultural self-confidence and family of the people. National sentiments and the inheritance of excellent traditional culture are of very important practical significance. As the intangible cultural heritage of mankind, Taijiquan is full of the genes and national wisdom of traditional Chinese culture. The cultural protection of Taijiquan is interpreted from the perspective of intangible cultural heritage, for the healthy development of Taijiquan, and to enhance the cultural self-confidence of the people, and to cultivate home country feelings, and inheriting excellent traditional culture has very important practical significance.